Transformasi Digital UMKM: Strategi Ekspansi Pasar dan Kemudahan Pembayaran di Era Digital - Nastiti, Arum (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2024)
Digital transformation is a strategic step for Micro, Small, and Medium Enterprises (MSMEs) to address the challenges of the digital era, such as global competition and changing consumer behavior. This article discusses the implementation of digital transformation through online ride-hailing applications (Grab, Gojek, and ShopeeFood) and digital payment systems (QRIS) to expand markets and improve transaction efficiency. Through a community service approach, training was conducted for home-based MSMEs to familiarize them with these technologies, select suitable platforms, and practice the registration process until account verification. The results indicate that MSMEs tend to prefer ShopeeFood due to its simpler registration process, lower fees, and direct integration with QRIS. Intensive assistance throughout the process demonstrated that digital technology could be effectively adopted, supporting MSMEs in reaching broader markets and enhancing customer experiences.